MYCOBACTERIUM TUBERCULOSIS SISTEM IMUN ALAMIAH TERKAIT PENERIMANYA - Jusak Nugraha (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Various attemp to investigate immune response towards tuberculosis has been done in order to eradicate or to make vaccination against tuberculosis (TB) effectively. Recently it is known that innate immunity has an important role in immunity to TB despite adaptive immune response, because it was proved that adaptive immune response alone was not sufficient to eradicate this microorganism thoroughly and completely in patient’s body. After Toll-Like Receptor (TLR) was found in the end of the 20th century, many progresses has been obtained in understanding about the activation of this innate immune response. But it is still needed to understand more deeply in the immune response to M. tuberculosis to lead the development of therapy or vaccination that bring into more precise target. The activation through TLR by parts of Mycobacterium induce cytoplasm protein adaptor MyD88 (Myeloid Differentiation factor 88). MyD88 has the function to activate NF- κB and secrete pro-inflammatory cytokine such as TNF-α, IL-6, IL-12. Involvement of MyD88 is not solely dependent of TLR2 receptor and there are another pathways to induce protective function of immunocompetent cells in TB.